Autologous Serum Skin Test as a Diagnostic Aid in Chronic Idiopathic Urticaria. (18th April 2013) - Al-Hamamy, Hayder R.; Hameed, Ammar F.; Abdulhadi, Asaad S.
Abstract : Background . Chronic urticaria is defined as urticaria persisting daily for more than six weeks. A significant number of patients had autoimmune basis where autologous serum skin test is widely used for detection of chronic autoimmune urticaria. Objectives . To estimate the frequency of autoimmune urticarial in Iraqi patients utilizing the autologous serum skin test and to evaluate its results with the variable clinical features of chronic idiopathic urticaria. Methods . In this prospective study, 54 patients with chronic idiopathic urticaria were investigated with autologous serum skin test where its results were examined with the different clinical parameters of chronic autoimmune urticaria. Results . Twenty two patients (40.7%) out of 54 patients with chronic idiopathic urticarial had positive autologous serum skin test. Statistical analysis of the clinical variables did not show a significant difference between patients with positive and negative autologous serum skin test except for the distribution of wheals on the face and extremities which was significantly associated with positive autologous serum skin test results ( P value 0.004). Conclusion . Autologous serum skin test is a simple, office-based test for detecting chronic autoimmune urticaria patients who have no distinctive clinical features differentiating them from chronic idiopathic urticaria patients.